Economic Complexity and Human Development: DEA performance measurement in Asia and Latin America - Diogo Ferraz; Hérick Fernando Moralles; Jéssica Suarez Campoli; Fabíola Cristina Ribeiro de Oliveira; Daisy Aparecida do Nascimento Rebelatto (Gest\~ao & Produç\~ao, 2018)
Economic growth is not the unique factor to explain human development. Due to that many authors have prioritized studies to measure the Human Development Index. However, these indices do not analyze how Economic Complexity can increase Human Development. The aim of this paper is to determine the efficiency of a set of nations from Latin America and Asia, to measure a country's performance in converting Economic Complexity into Human Development, between 2010 and 2014. The method used was Data Envelopment Analysis (DEA), through the Variable Returns of Scale (VRS) Model and Window Analysis. Results showed in 2014, all Asian countries were efficient except China and the Philippines, and Cuba was the benchmark for inefficient countries. Window Analysis showed Japan, Republic of Korea and Singapore were efficient over time. This result confirms the initial hypothesis of this article: the more complex countries are more efficient in generating Human Development. – – O crescimento econômico n\~ao é o único fator que explica o desenvolvimento humano. Neste aspecto, índices sobre a qualidade de vida têm sido recorrentes na literatura. Entretanto, estes índices n\~ao analisam como a complexidade econômica é convertida em desenvolvimento humano. O objetivo deste artigo é mensurar a eficiência dos países latino americanos e asiáticos em converter complexidade econômica em desenvolvimento humano, entre 2010 e 2014. O método utilizado foi o Data Envelopment Analysis (DEA), por meio do modelo de Retornos Variáveis à Escala (BCC) e Análise de Janela. Os resultados demonstraram que, em 2014, todos os países asiáticos foram eficientes, exceto a China e Filipinas. Neste ano, Cuba foi o país que mais serviu de benchmark para os países ineficientes. A análise em janela demonstrou que apenas Jap\~ao, Coréia do Sul e Singapura se mantiveram eficientes ao longo do tempo. Este resultado confirma a hipótese inicial deste artigo: economias mais complexas s\~ao mais eficientes em gerar desenvolvimento humano.
Keywords: O15; O32; 330; Data Envelopment Analysis (DEA); Window Analysis; Economic Complexity; Human Development